2018
DOI: 10.1017/s0952523817000359
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin expression in the cornea

Abstract: A unique class of intrinsically photosensitive retinal ganglion cells in mammalian retinae has been recently discovered and characterized. These neurons can generate visual signals in the absence of inputs from rods and cones, the conventional photoreceptors in the visual system. These light sensitive ganglion cells (mRGCs) express the non-rod, non-cone photopigment melanopsin and play well documented roles in modulating pupil responses to light, photoentrainment of circadian rhythms, mood, sleep and other ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
(51 reference statements)
2
22
0
Order By: Relevance
“…Thus, we checked for the presence of these non-visual opsins in neural trigeminal culture. By means of immunochemistry, we observed the presence of melanopsin in neuronal cell bodies, in line with Delwig et al [54]. Only some neurons exhibited melanopsin immunoreactivity, in agreement with Matynia et al, according to whom melanopsin is expressed overall in approximately 3% of TG neurons [26].…”
Section: Besides the Mitochondrial Respiratory Chain Opsins Are Alsosupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we checked for the presence of these non-visual opsins in neural trigeminal culture. By means of immunochemistry, we observed the presence of melanopsin in neuronal cell bodies, in line with Delwig et al [54]. Only some neurons exhibited melanopsin immunoreactivity, in agreement with Matynia et al, according to whom melanopsin is expressed overall in approximately 3% of TG neurons [26].…”
Section: Besides the Mitochondrial Respiratory Chain Opsins Are Alsosupporting
confidence: 92%
“…It has been recently reported that small number of neurons in the ophthalmic branch of trigeminal ganglia express melanopsin (opn4) and are intrinsically photosensitive [26]. Moreover, another recent study discovered the previously unrecognized localization of this photopigment in nerve fibers within the cornea [54]. Another non-visual photoreceptor, gaining today an increasing attention, is neuropsin (opn5).…”
Section: Besides the Mitochondrial Respiratory Chain Opsins Are Alsomentioning
confidence: 99%
“…Recently, melanopsin presence in the cornea and the crystalline lens was identified (Alkozi et al, 2017d;Delwig et al, 2018). Studies using human crystalline epithelial cells showed that different light conditions were able to produce changes in melatonin levels in the extracellular medium, in fact, blue light activated melanopsin protein leading to melatonin reduction in comparison to cells incubated under constant darkness or red light.…”
Section: Melatonin: a Relevant Player In Iop Regulationmentioning
confidence: 99%
“…42,43 Whether light activates melanopsin-expressing trigeminal neurons is equivocal. 41,44 Other potential sources are choroidal blood vessels or melanocytes as melanopsin has been identified in mouse aorta and in cultured chicken melanocytes. 45,46 Regarding potential function, the normal light-induced increase in choroidal thickness in mice is not observed with systemic knockout of melanopsin, 47 suggesting that melanopsin might regulate diurnal or defocus-induced choroidal thickness alterations.…”
Section: Opn4m Expression In the Choroidmentioning
confidence: 99%